"أهمية التحقيق المحاسبي في مراجعة الأسس الضريبية وتعزيز الرقابة الجبائية -دراسة حالة مركز الضرائب بالوادي خلال الفترة 2017-2020-" - عبد الحافظ الأطرش; بوبكر غومة; السعيد زغدي; عبد الحافظ موم (جامعة الوادي University Of Eloued, 2024)
"يعد التحقيق المحاسبي من أهم الوسائل التي تستخدمها الإدارة الجبائية للتأكد من صحة الأسس الضريبية المصرح بها من قبل المكلفين والتي تتيح لها الكشف عن عمليات التلاعب والتظليل التي ينوي المكلفون التهرب من سداد التزاماتهم تجاه الإدارة الجبائية، حيث يعد التحقيق المحاسبي أداة فعالة لتحديد الأسس الضريبية بشكل علمي ومنظم يعزز من أهمية الرقابة الجبائية ويحفظ حقوق الخزينة العامة من الضياع، ويزيد بشكل غير مباشر من مستوى الامتثال لأحكام التشريعات الضريبية. تهدف هذه الدراسة إلى إبراز أهمية التحقيق المحاسبي في مراجعة الأسس الضريبية وتعزيز الرقابة الجبائية، وذلك باستخدام دراسة تطبيقية على مستوى مركز الضرائب بالوادي، وذلك للتعرف على كافة إجراءات التحقيق اللازمة للوصول إلى الأهداف المرجوة، حيث خلصت هذه الدراسة إلى أن التحقيق المحاسبي يعد من أهم أشكال الرقابة الجبائية، كما تقوم بمراجعة الأسس الضريبية واسترداد مبالغ مالية مهمة تساهم في تحسين الإيرادات الضريبية للدولة." " The accounting investigation is one of the most important means used by the tax administration to ensure the validity of the tax bases authorized by taxpayers, which allows it to discover the manipulation and shading operations that taxpayers resort to evade paying their obligations towards the tax administration, as the accounting investigation is an effective tool to determine the tax bases in an organized scientific manner that enhances the importance of tax control and preserves the rights of the public treasury from loss, and indirectly increases the level of compliance with the provisions of tax legislation. This study aims to highlight the importance of accounting investigation in reviewing tax bases and strengthening tax control, using an applied study at the level of the tax center in the valley, in order to identify all the investigation procedures necessary to reach the desired goals, as this study concluded that accounting investigation is one of the most important forms of tax control, as it reviews the tax foundations and recovers important amounts of money that contribute to improving the state's tax revenue."
مذكرة ماستر
Keywords: التحقيق المحاسبي- الأسس الضريبية-الرقابة الجبائية.; Accounting investigation-tax bases-tax control.